Expression of NanoLuc Luciferase in Listeria innocua for Development of Biofilm Assay - Berlec, Aleš; Janež, Nika; Sterniša, Meta; Klančnik, Anja; Sabotič, Jerica (Frontiers in Microbiology, 2021)
Studies of biofilm formation by bacteria are crucial for understanding bacterial resistance and for development of novel antibacterial strategies. We have developed a new bioluminescence biofilm assay for Listeria innocua, which is considered a non-pathogenic surrogate for Listeria monocytogenes. L. innocua was transformed with a plasmid for inducible expression of NanoLuc luciferase (Nluc). Concentration-dependent bioluminescence signals were obtained over a concentration range of more than three log units. This biofilm assay enables absolute quantification of bacterial cells, with the necessary validation. For biofilm detection and quantification, this ‘Nluc bioluminescence’ method has sensitivity of 1.0 ×104 and 3.0 ×104 colony forming units (CFU)/mL, respectively, with a dynamic range of 1.0 ×104 CFU/mL to 5.0 ×107 CFU/mL. These are accompanied by good precision (coefficient of variation, <8%) and acceptable accuracy (relative error for most samples, <15%). This novel method was applied to assess temporal biofilm formation of L. innocua as a function of concentration of inoculant, in comparison with conventional plating and CFU counting, the crystal violet assay, and the resazurin fluorescence assay. Good correlation (r = 0.9684) of this Nluc bioluminescence assay was obtained with CFU counting. The limitations of this Nluc bioluminescence assay include genetic engineering of bacteria and relatively high cost, while the advantages included direct detection, absolute cell quantification, broad dynamic range, low time requirement, and high sensitivity. Nluc-based detection of L. innocua should therefore be considered as a viable alternative or a complement to existing methods.